Torque improvement of PM motor with semi-cycle stator design using 2D-finite element analysis - Kwang T. C.; Mohd Luqman Mohd Jamil; Auzani Jidin (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper presents sizing approaches to improve output torque performance in PM motor when partial stator body is removed. As the output torque performance is directly proportional to the electric loading, Q, modification on stator geometry affects the output torque performance and special procedures have to be taken to restore the desired output torque capability. Influences of split ratio, tooth body width, airgap and magnet thickness of  magnet in PM motor with asymmetry stator design are carried out and the performance verification are referred to the back-emf, average output torque, torque ripple as well as cogging torque. From the investigation using 2D-Finite Element Analysis, optimum size of tooth body width and optimum number of coil turns result better output torque while other sizing approaches result no significant change as quick saturation took place.